From "Trece badaladas" to "Trece campanadas", or how a novel and a movie emerged from a single plot (II) - Rivero Grandoso, Javier (Madrygal. Revista de Estudios Gallegos, 2013)
The creative process that generated Suso de Toro’s Trece badaladas and Trece campanadas, directed by Xavier Villaverde, departs markedly from what is usual in such cases, since the film adaptation is usually done when the literary work is a best-seller in order to make sure, thus, that it attracts the interest of a particular audience. In this case, Suso de Toro’s novel and Villaverde’s film came up almost at once, so that the publication of the book took place just a few months before the premiere of the film. In this paper, we outline the story of a project that resulted in two very different works and we analyze the points of agreement and disagreement between them.
Keywords: literature and cinema; adaptation; Suso de Toro; Xavier Villaverde